PENDIDIKAN ISLAM MODERAT DAN IMPLIKASINYA PERSPEKTIF KH. ALI MAKSUM - Laksono, Dimas Setiadi; Shohib, Muhammad (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
The escalation of radicalism and intolerance in Indonesia demands a transformation of the educational paradigm capable of bridging the polarization between conservative and liberal religious thought. This study aims to explore the concept of moderate Islamic education from the perspective of KH. Ali Maksum and analyze its implications for the development of the national Islamic education system. Using a qualitative approach with a literature study design, this study examines in-depth the authoritative works of this figure, particularly the book "Hujjah Ahlus Sunnah wal Jamaah," through content and historical analysis techniques. The main findings indicate that KH. Ali Maksum's construction of moderation is built on a proportional balance between intellectual and spiritual dimensions, which includes tolerance for differences in jurisprudence (ikhtilaf), strengthening rational faith, and prioritizing social piety. The implications of this thinking for education in Indonesia include the urgency of integrating religious and science curricula, instilling inclusive values, and strengthening character based on global ethics. This study concludes that the pedagogical ideas of KH. Ali Maksum offers a comprehensive framework as a theological bulwark against extremism, while simultaneously positioning educational institutions as laboratories of moderation, effectively producing a generation of adaptability, integrity, and the ability to maintain harmony in a multicultural society. ABSTRAKEskalasi radikalisme dan intoleransi di Indonesia menuntut transformasi paradigma pendidikan yang mampu menjembatani polarisasi antara pemikiran keagamaan konservatif dan liberal. Penelitian ini bertujuan untuk mengeksplorasi konsep pendidikan Islam moderat perspektif KH. Ali Maksum serta menganalisis implikasinya bagi pengembangan sistem pendidikan Islam nasional. Menggunakan pendekatan kualitatif dengan desain studi kepustakaan, penelitian ini menelaah secara mendalam karya-karya otoritatif tokoh, khususnya kitab Hujjah Ahlus Sunnah wal Jamaah, melalui teknik analisis isi dan sejarah. Temuan utama menunjukkan bahwa konstruksi moderasi KH. Ali Maksum dibangun di atas keseimbangan proporsional antara dimensi intelektual dan spiritual, yang mencakup sikap toleran terhadap perbedaan fikih (ikhtilaf), penguatan akidah yang rasional, serta prioritas pada kesalehan sosial. Implikasi pemikiran tersebut terhadap pendidikan di Indonesia meliputi urgensi integrasi kurikulum ilmu agama dan sains, penanaman nilai inklusivitas, serta penguatan karakter berbasis etika global. Penelitian ini menyimpulkan bahwa gagasan pedagogis KH. Ali Maksum menawarkan kerangka kerja komprehensif sebagai benteng teologis melawan ekstremisme, sekaligus memposisikan institusi pendidikan sebagai laboratorium moderasi yang efektif mencetak generasi adaptif, berintegritas, dan mampu merawat harmoni dalam masyarakat multikultural.